2017
DOI: 10.1042/cs20160571
|View full text |Cite
|
Sign up to set email alerts
|

miR-378 reduces mesangial hypertrophy and kidney tubular fibrosis via MAPK signalling

Abstract: The regulatory role of a novel miRNA, , was determined in the development of fibrosis through repression of the MAPK1 pathway, and fibrotic gene expression was examined in streptozotocin (STZ)-induced diabetic mice at 18 weeks or in unilateral ureteral obstruction (UUO) mice at 7 days. transfection of proximal tubular epithelial cells, NRK52E and mesangial cells was assessed with/without endogenous knockdown using the locked nucleic acid (LNA) inhibitor. NRK52E cells were co-transfected with the mothers agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…In the IL-17 signaling pathway, Th17 is a new type of proinflammatory CD4 + T-effector cells, which are different from Th1 and Th2 cell lines [ 43 ]. The increase in Th17 cytokines (such as IL-17A) may promote the secretion of proinflammatory factors and infiltration of macrophages and aggravate the diabetes-induced renal damage in DN [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the IL-17 signaling pathway, Th17 is a new type of proinflammatory CD4 + T-effector cells, which are different from Th1 and Th2 cell lines [ 43 ]. The increase in Th17 cytokines (such as IL-17A) may promote the secretion of proinflammatory factors and infiltration of macrophages and aggravate the diabetes-induced renal damage in DN [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have demonstrated that TGF-β1 modulates several microRNAs (miR) to promote renal fibrosis. TGF-β1 has been shown to upregulate miR-21 and miR-192, -377, -382 and -491-5, but downregulates miR-29, -200 and -378 causing renal fibrogenesis [114][115][116]. The miR-21 level is markedly elevated in fibrotic kidneys [117,118], and its inhibition has been shown to attenuate ECM and retard the progressive renal fibrosis [119,120].…”
Section: Role Of Tgf-β/smad-dependent Micrornas In Renal Fibrosismentioning
confidence: 99%
“…Nevertheless, miR-378 is highly decreased in DN and regulates the expression of fibrotic genes and the MAPK1 pathway. Overexpression of miR-378 could inhibit MC expansion and proliferation, thereby attenuating kidney cell fibrosis and mesangial hypertrophy [61]. These findings suggested that miRNAs are involved in the development process of DN through modulating cell proliferation.…”
Section: Role Of Mirnas In Cell Proliferation In Dnmentioning
confidence: 90%